Contrast-enhanced ultrasonography for the management of portal hypertension in cirrhosis - Maruyama, Hitoshi; Tobari, Maki; Nagamatsu, Hiroaki; Shiina, Suichiro; Yamaguchi, Tadashi (Frontiers in Medicine, 2022)
Portal hypertension is a major pathophysiological condition in patients with cirrhosis. This accounts for the occurrence and severity of the various manifestations. The degree is determined by the portal pressure or hepatic venous pressure gradients, both of which are obtained by invasive interventional radiological procedures. Ultrasound (US) is a simple and minimally invasive imaging modality for the diagnosis of liver diseases. Owing to the availability of microbubble-based contrast agents and the development of imaging modes corresponding to contrast effects, contrast-enhanced US (CEUS) has become popular worldwide for the detailed evaluation of hepatic hemodynamics, diffuse liver disease, and focal hepatic lesions. Recent advancements in digital technology have enabled contrast-based demonstrations with improved resolution, leading to a wider range of applications. This review article describes the current role, benefits, and limitations of CEUS in the management of portal hypertension.